The optimization of red pigment by monascus purpureus FTC 5356 in solid state fermentation - Nur Shazwani, Nadzri (2012)
Monascus red pigment had been found to have capability to give natural color that meet demand in the industries. The objective of this research is to identify the optimize condition of red pigment production in solid state fermentation by Monascus Purpureus FTC 5356 using local agricultural products as a substrate. The substrates used in this research were banana, corn, papaya, coconut meat, white rice, pumpkin and guava. In determining the best substrates, the initial moisture content was set up at 50%, pH 6 for 10 days at 30°C. Among the local agricultural products, it was identified that banana is the best with 0.3390AU/g.day of red pigment production. The optimum condition for the pigment production in parameter study was 50% of initial moisture content and addition of 1.8% of nitrogen source to the substrate. The optimum growth for pigment production was 7 days. The further experiment will be conducted using Central Composite Design (CCD) of Response Surface Methodology (RSM) by setting parameter of nitrogen source concentration and moisture content of the substrate in producing high pigment production.